Recovery and practice-based evidence: reconnecting the diverging discourses in mental health. Issue 1 (13th February 2017) - Collins, Padraig; Crowe, Sarah
Abstract : Purpose: The purpose of this paper is to explore the discourses which exist around the alleviation of mental distress, from the different perspective of mental health professionals and service users. It then looks at the use of "practice-based evidence" as a means of bringing together these two diverging discourses. Design/methodology/approach: Literature on the discourses which exist around the cause and treatment of mental distress, from the perspective of professionals and service users, is first explored. Differences between these two discourses are identified, as are theoretical and practical limitations of current professional diagnostic and treatment paradigms. Finally the use of practice-based evidence as a means of bridging the gap between these two discourses is outlined. Findings: This paper highlights marked differences between the discourse which exists for professionals, and that for service users, around alleviating mental distress. The use of practice-based evidence is explored, not only as a means of bringing these two varying discourses together, but also as a tool which could help to improve treatment outcome in a way which is more inclusive of service users and fits with both empiricism and a broader recovery ethos. Originality/value: This paper applies a "practice-based evidence" approach to bringing together the divergent perspectives regarding mental health of service providers and users. In doing so it provides a practical and pragmatic approach to true collaborative working.